Phytotelmatomyia, a new Neotropical subgenus of Culex (Diptera: Culicidae) - Rossi, Gustavo C.; Harbach, Ralph E. (Zootaxa, 2008)
Phytotelmatomyia, a new subgenus in the Neotropical Region, is proposed for four described species, including Cx. castroi Casal & García, Cx. hepperi Casal & García, Cx. machadoi da Silva Mattos, da Silveira Guedes & Hamilton Xavier, and Cx. renatoi Lane & Ramalho (type species), and two potentially new species without formal Latin names. Monophyly of the group is supported by cladistic analyses of morphological data. Phytotelmatomyia is separated and distinguished from subgenera Culex and Phenacomyia. Diagnostic and differential characters of the male genitalia, larvae, and pupae of the three subgenera are tabulated and illustrated. Bionomics and distributional data are provided for Phytotelmatomyia species.